2004
DOI: 10.1161/01.str.0000128530.75424.63
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Contrast Magnetic Resonance Imaging Measurements of Cerebral Autoregulation With a Breath-Hold Challenge

Abstract: Background and Purpose-Vasomotor reactivity (VMR) testing can identify patients with hemodynamically critical cerebrovascular disease. The use of VMR has been limited by the invasiveness of most of the available methods and of acetazolamide as VMR stimulus. In the present study, we evaluated a completely noninvasive VMR approach by combining quantitative phase-contrast magnetic resonance imaging (MRI) with a breath-hold challenge. Methods-Volume flow rates in the right and left internal carotid artery (ICA), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 40 publications
1
47
0
Order By: Relevance
“…33 Animal and human studies have both demonstrated significant CBF increases in response to hypercapnia. [5][6][7]12,13,[16][17][18][33][34][35][36][37][38][39] This reaction has been exploited with tests such as the hypercapnia challenge to evaluate cerebrovascular reserve. 2,7,8 Previous human studies demonstrated up to a 200% increase in CBF as pCO 2 was raised experimentally.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…33 Animal and human studies have both demonstrated significant CBF increases in response to hypercapnia. [5][6][7]12,13,[16][17][18][33][34][35][36][37][38][39] This reaction has been exploited with tests such as the hypercapnia challenge to evaluate cerebrovascular reserve. 2,7,8 Previous human studies demonstrated up to a 200% increase in CBF as pCO 2 was raised experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Gas mixtures with elevated concentrations of carbon dioxide (CO 2 ) are commonly used in both the research and clinical settings to evaluate cerebrovascular reserve, most frequently in patients with stenotic or occlusive cerebrovascular disease before extracranial-to-intracranial bypass. 2,7,8 Even small increases in the partial pressure of CO 2 (pCO 2 ) on the order of 5 to 6 mm Hg are capable of generating appreciable changes on perfusion imaging. 3,4,[7][8][9][10][11][12][13] Techniques such as transcranial Doppler, nuclear medicine positronemission tomography (PET) and single-photon emission CT, angiography, phase-contrast MR imaging, and arterial spinlabeled (ASL) MR perfusion have been used to evaluate the experimental hypercapnic effect on cerebral perfusion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The potential effect of CO 2 inhalation on neural activity is not clear. Existing literature mostly presumes that altering CO 2 partial pressure has no effect on brain tissue and the use of CO 2 inhalation or the carbonic anhydrase inhibitor acetazolamide can be considered a purely vascular challenge to assess cerebrovascular reserve (de Boorder et al, 2004) or to calibrate functional magnetic resonance imaging (fMRI) signal (Chiarelli et al, 2007;Davis et al, 1998;Kim and Ugurbil, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 qMRA has been used to determine the total cerebral blood flow (CBF), [3][4][5] the effect of age and sex on the total CBF, 6 distribution of CBF in the circle of Willis, 7 and cerebral autoregulation, 8 as well as to evaluate various cerebrovascular disorders. [9][10][11][12][13][14][15][16] The range of blood flow for a healthy individual vessel in the brain, however, can be quite diverse because of inherent vascular anatomy and/or anatomic variations in the circle of Willis.…”
mentioning
confidence: 99%